Checkpoint Maths 1 - "Pimentel, Ric" (Hodder Education: Dubai, 2014)
This new edition has been completely updated to match the revised Cambridge Secondary 1 Curriculum Framework, the Cambridge Checkpoint Tests and the Cambridge Progression Tests for stage 7
Keywords: Mathematics - Textbook